التحولات العالمية في الأنظمة البيئية للشركات الناشئة 2020-2025 - مداح ،عبد الهادي; بن خيرة ،ميلود (University of Eloued جامعة الوادي, 2025)
This paper highlights the most significant developments affecting startup ecosystems worldwide from 2020 to 2025, in light of the proliferation of artificial intelligence tools and applications, as well as the acceleration in investment and funding for startups in the fields of artificial intelligence and emerging technologies. A descriptive-analytical approach was applied to examine, describe, and analyze various indicators reflecting these transformations throughout the study period. Through this study, we found: • A sharp decline in the value of the global startup ecosystem in 2025, declining by 31% overall. • The average change in the value of the top 20 ecosystems worldwide also declined by 24%. • Early-stage funding shrank, while late-stage funding performed slightly better in terms of funding value. • The United States and China represent 56% of the global startup ecosystem's value. • We found that 90% of AI funding is currently concentrated in the United States and China. • The Seoul, South Korea, ecosystem performed well, ranking 16th globally in 2021 and 8th in 2025. • Singapore's ecosystem was ranked 17th globally in 2021, 8th in 2024, and 9th in 2025.
مقال
Keywords: شركات ناشئة; أنظمة بيئية للشركات الناشئة; ذكاء اصطناعي; تكنولوجيا